2016
DOI: 10.1590/1518-8345.0260.2736
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hypoalbuminemia and nutritional issues in hospitalized elders

Abstract: Objective: to estimate the prevalence of hypoalbuminemia in hospitalized elders, related to socio-demographic variables, nutritional status and length of stay. Methods: crosscutting study with 200 patients hospitalized in a large hospital in the South of Brazil during three months. Evaluations, lab tests and interviews through questionnaires were performed. Results: the average albuminemia was 2,9 ± 0,5g/dL. Hypoalbuminemia was diagnosed in 173 subjects (87%) and was absent in 27 (13%) that have normal albumin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
31
0
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 10 publications
2
31
0
12
Order By: Relevance
“…However, in a subset of patients 60 years of age and older assessed with the Mini Nutritional Assessment, 32.9% were considered to be at risk of malnourishment, and 11.0% were considered to be malnourished (8). Employing the Mini Nutritional Assessment and a serum albumin assay, in a study with 200 hospitalized elderly patients (mean age, 72.6 ± 8.3 years) at a university hospital in Erechin, RS, Brock et al (2016) (9) found that 87% of the assessed patients had hypoalbuminemia, 43% were at risk of malnutrition, and 21.5% were malnourished (9).…”
Section: Resultsmentioning
confidence: 99%
“…However, in a subset of patients 60 years of age and older assessed with the Mini Nutritional Assessment, 32.9% were considered to be at risk of malnourishment, and 11.0% were considered to be malnourished (8). Employing the Mini Nutritional Assessment and a serum albumin assay, in a study with 200 hospitalized elderly patients (mean age, 72.6 ± 8.3 years) at a university hospital in Erechin, RS, Brock et al (2016) (9) found that 87% of the assessed patients had hypoalbuminemia, 43% were at risk of malnutrition, and 21.5% were malnourished (9).…”
Section: Resultsmentioning
confidence: 99%
“…Los adultos mayores que tienen compromiso proteico principalmente de albúmina presentan mayor riesgo de malnutrición, así lo confirma la American College of Surgery, la cual observa una asociación entre hipoalbuminemia y malnutrición y la correlaciona con complicaciones en geriátricos con trauma HR 2,1 (IC95%: 1,1-3,8) 23 . La prevalencia de hipoalbuminemia se muestra elevada, probablemente secundario a una ingesta proteica inadecuada, trastornos en la deglución, alteraciones gastrointestinales y/o endocrinológicas frecuentes en este grupo etario, afectando aproximadamente al 9% de los adultos mayores p<0,001, así lo demuestra Brock et al 2016, en su estudio de prevalencia de hipoalbuminemia y aspectos nutricionales pacientes geriátricos 24 . En el presente estudio se corrobora esta asociación RP 2,87 (IC95%: 1,08-4,58; p<0,001).…”
Section: Discussionunclassified
“…Aging changes the liver, and the ability to synthesize albumin and other proteins is reduced in elderly people [28]. Elderly people also exhibit decreased secretion and delayed excretion of bile [29].…”
Section: Discussionmentioning
confidence: 99%